Characteristics and antibiogram of airborne bacterial communities (Bangladesh Journal of Botany, 2020)
Composition and concentration of the bacterial communities in air of using a culture-dependent plate exposure technique and air sampling with filter were analysed. An average value of 2.8 x 103 bacterial CFU/m3 was found in different seasons. A total of 8 bacterial genera were identified among 58 species. The most predominant bacteria were Bacillus (73%), Planococcus (9%), Staphylococcus (6%), Micrococcus (4%), Deinococcus (2%), Arthrobacter (2%), Microbacterium (2%), and Exiguobacterium (2%). The distribution of predominant airborne bacteria varied greatly between different sampling sites and seasons and was limited by environmental parameters, as well as human activities.